Combined laparoscopic and hysteroscopic management of cesarean scar pregnancy with temporary occlusion of bilateral internal iliac arteries: A case report and literature review. Issue 32 (August 2018) - Li, Jianqiong; Li, Xia; Yu, Hailan; Zhang, Xiao; Xu, Wenzhi; Yang, Jianhua
Abstract: Rationale: Cesarean scar pregnancy is a rare event that carries a risk of heavy hemorrhage and emergency hysterectomy. Many treatment modalities have been reported, but with no consensus. Here we report a case of combined laparoscopic and hysteroscopic treatment with temporary occlusion of the bilateral internal iliac arteries. Patient concerns: A 28-year-old woman presented with amenorrhea diagnosed as an 11-week cesarean scar pregnancy after an unsuccessful abortion. The patient's serum human chorionic gonadotropin level was 40, 542 mIU/mL. Magnetic resonance imaging revealed a mass measuring 5 × 4.5 cm over the anterior uterine isthmus. Diagnose: Type III cesarean pregnancy. Interventions: Diagnostic and operative laparoscopy were performed to remove the pregnancy tissue and repair the scar dehiscence after temporary occlusion of the bilateral internal iliac arteries, followed by hysteroscopy to confirm no pregnancy remnants and to free intrauterine adhesions. Outcomes: Intraoperative and postoperative bleeding were minimal. The postoperative recovery was uneventful. Human chorionic gonadotropin normalized after 3 weeks. Lessons: Temporary occlusion of the bilateral internal iliac arteries seems to be a good strategy to reduce hemorrhage in cesarean scar pregnancy. Hysteroscopy is necessary to deal with intrauterine lesions.